Identifying the Dynamic Connectedness between Propane and Oil Prices: Evidence from Wavelet Analysis - Hung, Ngo Thai (International Journal of Energy Economics and Policy, 2020)
This paper takes into account the LPG markets and aims to examine the short run and long run dependencies between crude oil and propane prices during the period 2006-2018. Our empirical study is based on the wavelet transform approach, which allows us to evaluate the co-movement in both time-frequency spaces. The techniques employed on the dataset includes maximal overlap discrete wavelet transform, wavelet covariance, wavelet correlation, continuous wavelet power spectrum, wavelet coherence and wavelet-based Granger causality tests to measure the intercorrelation between crude oil and propane markets. The findings suggest that the existence of strong interconnectedness between crude oil and propane series in the short and medium run. However, there is a unidirectional impact of propane returns on crude oil markets in the very long term. Furthermore, we construct the wavelet-based Granger causality test at different time scales to provide additional support to our nexus results. Our results provide significant implications for policymakers, portfolio managers, and practitioners who are invited to consider the dynamics of return and volatility spillovers between crude oil and propane markets to create sound policy based on a clear comprehension of the transmission between these markets. Keywords: Crude oil, liquefied petroleum gas, co-movement, wavelet analysis, propane. JEL classifications: G13, C22, F30 DOI: https://doi.org/10.32479/ijeep.9631